Environmental Sustainability Assessment of Cold Storage Panel Production - Emrah Yılmaz (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2024)
Today's ever-increasing environmental sustainability concerns have led to a major shift in construction sites and industrial sectors. In this context, the choice of construction materials for important structures such as cold storages plays an important role in terms of both environmental impacts and energy efficiency. The aim of this study is to evaluate the environmental loads of cold storage panels with thicknesses of 80 mm, 100 mm, 120 mm, 150 mm, 180 mm and 200 mm. In order to reveal the production inputs that cause these loads, the environmental effects were examined specifically for the 100 mm thick cold storage panel. Environmental impacts were analyzed using the Life Cycle Assessment (LCA) method in accordance with the ISO 14040/44 methodology as a system boundary "cradle to gate". This study focused on three different environmental impact categories of cold storage panels produced in Türkiye: global warming potential (GWP), cumulative energy demand (CED) and water footprint. In the evaluation of environmental impacts, production inventory information obtained from the panel manufacturer was used. For analyses, Simapro v. 8.5 LCA software was used. Analysis results show that the use of galvanized sheet metal in cold storage panel production is a hot spot in terms of global warming effect. It has been determined that the largest share in the water footprint belongs to polyurethane used as insulation material. Additionally, according to the CED, non-renewable fossil and non-renewable nuclear were determined to be the most affected categories, and the use of galvanized sheet metal and polyurethane were determined to be the most important hot spots in terms of non-renewable and renewable resources. To help improve the environmental performance of the cold storage panel, it is recommended to use bio-based and less environmentally impactful raw materials in production and to measure their environmental impact on a life cycle basis from cradle to grave.